Research and thesis: if only I had known - Talib, Othman (MPWS Rich Resources, 2014)
This book should be owned and read by all undergraduate, master and PhD students who are currently involved in thesis writing or planing to embark on conducting research. This book is must-have for tutors, research assistant and lecturer in higher institutions, especially those who involved in student supervision the book contains the nuts and bolts of carrying out research ang thesis writing. No other copy in the bookstore has ever been published with practical examples using easy to understand language. Definitely the ultimate guide for those who have lost their way in research.